Prognostic value of C-reactive protein-to-albumin ratio and inflammatory markers in esophageal cancer patients treated with chemoradiotherapy - Berrin Inanc; Ozlem Mermut (National Scientific Medical Center, 2021)
Background: This retrospective research, it was aimed to evaluate disease-free survival (DFS)  using inflammatory markers in esophageal cancer patients who received chemoradiotherapy (CRT). Methods: A total of 67 patients who received standard curative chemoradiotherapy for esophageal cancer were included in the study between 2011-2018. The patient, treatment characteristics, and pretreatment inflammatory markers were obtained from the patient's file. Results : Median follow up time was 18 months (6-72 months). ROC curve analyses showed the C-Reactive Protein-to-Albumin (CAR) cut-off  value  0.9 for  DFS (AUC:78.8%; sensitivity: 85%; specificity; 67.5%). 2-year disease free survival for CAR ≥0.9 and CAR  <0.9 were 45.7% and 78%, respectively ( P=0.035). The radiation doses >50Gy (versus <50Gy, p=0.027) and  CAR ratio < 0.9 (versus ≥ 0.9, p=0.005)  appeared significant  associates of better  DFS in univariate  analyses, but the age, gender, stage, localization, neutrophil-to-lympocyte ratio (NLR) and platelet-to-lymhocyte ratio (PLR) were no statistically significant (p>0.005).On the multivariate logistic analysis, our results  showed that CAR < 0.9 [hazard ratio (HR) 1.29; 95% confidence interval [CI], 1.336-2.946; P = 0.014];  and radiation dose >50 Gy (HR 0.91; 95% CI, 1.229-4.997; P = 0.027) independent prognostic indictors. Conclusion: Our study found that the C-Reactive Protein/Albumin ratio is easy to apply and maybe a promising marker to predict disease-free survival in esophageal cancer patients who received chemoradiotherapy.